If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8x + -36 = 3x Reorder the terms: -36 + 6x + 8x = 3x Combine like terms: 6x + 8x = 14x -36 + 14x = 3x Solving -36 + 14x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -36 + 14x + -3x = 3x + -3x Combine like terms: 14x + -3x = 11x -36 + 11x = 3x + -3x Combine like terms: 3x + -3x = 0 -36 + 11x = 0 Add '36' to each side of the equation. -36 + 36 + 11x = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 11x = 0 + 36 11x = 0 + 36 Combine like terms: 0 + 36 = 36 11x = 36 Divide each side by '11'. x = 3.272727273 Simplifying x = 3.272727273
| 6n-3(4-n)=-30 | | 8(4-3p)=4(3-5p)+4p | | 4x-6=-6-4 | | 0=20x^2+10x | | 1.5x-1=3.5 | | 0=20x^2+10 | | 1/2(y+7)=17 | | -4x-11x=75 | | 1.5x-1=-4 | | 307=2x-57 | | x^2-13x-90=8 | | 3x-11x=-48 | | 3/4=x/500 | | -2(x-3)=-2x+6 | | 7-2[-6-(2-5)]= | | 4x+8y=-32 | | .33(10x-5)=3 | | 1/2y+12=6 | | 15x+7=-23 | | 5e+2=2e-2 | | g(x)=-log(x) | | 12x=5/6 | | 12x+5/6 | | 12v^2=-10v-10 | | -9(z+3)-5(2z+10)= | | 8x+4-2x=-5+4x | | b^2-13=0 | | 15+1/4x=2 | | 8g+4-6g=-5 | | 16m=ft | | 4n^2-9=35 | | 8g+4-27=81 |